Smart Energy Meter for Energy Cost Analysis of Grid - Sachin T Chede; Sourabh S Nagane, Akash N Shelar, Pratik S Thorve, Payal S. Burande (Journal of Power Electronics and Devices, 2021)
A smart energy meter is a computerized electric meter that actions the power age, utilization and gives other extra highlights, for example, progressed charging framework and high precision which makes it more profitable than the conventional energy meter. The proposed shrewd meter model is checked by planning a proper circuit and related equipment. The equipment is planned to utilize a GSM, GPRS, and Arduino. This meter can measure energy and send the information to a specialist co-op, which can store the information and notify customers through SMS or the internet. Because of the increase in both the population and the mechanical turn of events, there is a growing interest in energy. Customers should be more conscious about their energy use to increase energy efficiency. Recently, utilities have gained prominence. To limit the line at the energy meter charging counters and to confine the use of energy meter naturally, if the bill isn't paid. The venture likewise targets proposing a framework that will lessen the deficiency of force and income because of force burglaries and other criminal operations. The working framework receives a new idea of "Prepaid Energy Meter". The GSM innovation is utilized with the goal that the customer would get messages about the utilization of force (in watts) and if it arrives at the base sum, it would naturally make the purchaser aware of re-energize. This innovation holds useful for all power circulation organizations, private networks, IT parks, and self-containing lodging projects. The execution of this undertaking will help in better energy the board, preservation of energy, and in getting rid of the superfluous issues over erroneous charging. The proposed metering framework is more favorable than the customary metering framework which will lessen the labor, cost, and time.